A molecular dynamics study on sintering behavior and densification characterization of nanocopper. Issue 1 (1st December 2022) - Shi, Jingmin; Xiao, Wei; Wang, Jianwei; Yang, Hui
Abstract: The technical problem of copper additive manufacturing is expected to be solved through the size effect of nanomaterials. The molecular dynamics method was employed to understand the laser sintering process of single-crystal copper nanoparticles. Based on a theoretical characterization of the densification of nanocopper sintering developed at present and the prediction of the melting point of nanocopper, the sintering and densification behaviors of copper nanoparticles with different sizes at different sintering temperatures were investigated. It is finally concluded that the densification of the nanocopper sinter can reach up to 95% under the condition of sintering temperature below the melting point of the nanocopper.